2018
DOI: 10.1590/1806-9282.64.12.1069
|View full text |Cite
|
Sign up to set email alerts
|

Fibrin sealant repair of a double-necked femoral pseudoaneurysm

Abstract: SUMMARY Pseudoaneurysms are rare, but femoral artery false aneurysms have increased in recent decades. They are related to endovascular procedures performed on patients with increased risk for this complication. Pseudoaneurysms generally present with only one neck. This paper describes a femoral artery pseudoaneurysm with two necks that occurred after an endovascular procedure and was successfully treated by duplex-guided fibrin sealant. Pseudoaneurysms are rare, but femoral artery pseudoaneurysms have increas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…7 Pseudoaneurysms vary in size and shape and can be a single lobe, multi-lobed, and can communicate with the feeding artery by more than one connecting neck. 8,9…”
Section: Discussionmentioning
confidence: 99%
“…7 Pseudoaneurysms vary in size and shape and can be a single lobe, multi-lobed, and can communicate with the feeding artery by more than one connecting neck. 8,9…”
Section: Discussionmentioning
confidence: 99%
“…If it is difficult to determine the specific location and extent of the leak, try extensively using adhesives in the wound, such as Tachosil, Fibrin glue, fibrin sealant combined with fibrinolysis inhibitor, Bioglue [39][40][41][42][43][44], etc., to cure all potential leaks during surgery. Fibrin glue has been used clinically for nearly 40 years, but some research results have shown that in the treatment of lymphatic leakage in other parts, it can not reduce the drainage of lymphatic leakage or shorten the time of catheterization [45].…”
Section: Intrawound Adhesives and Other Non-surgical Treatmentsmentioning
confidence: 99%
“…As the first attempt with an endovascular approach did not exclude the second option, a minimal invasive treatment was tried, together with the infusion of thrombin. Thrombin injection has been described and is widely used to treat post-function arterial pseudoaneurysms, 10,11 but not to treat infectious pseudoaneurysms. In our case it allowed to prevent the backbleeding of the profunda as a safe way to promote the clot formation inside the pseudoaneurysm.…”
mentioning
confidence: 99%